Survey of students’ motivation to learn mathematics and the teachers’ methods of knowledge assessment - Gudelytė, Laura; Krylovas, Aleksandras; Laukevičius, Tadas (Lietuvos matematikos rinkinys, 2011)
The knowledge of basic mathematics of 178 students of second year of public administration at Mykolas Romeris University was tested. The analysis of students’ motivation and their knowledge of basic mathematics given in school (exams) and survey of the impact of teacher’s subjectivity to the final evaluation of knowledge is provided. Empirical analysis of data shows that students’ motivation has a direct impact to their knowledge and that provided students’ knowledge testing eliminates the subjectivity from the knowledge evaluation.